Avaliação da locomoção de cães submetidos à ostectomia unilateral da cabeça e colo femorais - Conti, Juliano Bortolo De [UNESP] (2013)
The aim of this study was to evaluate dogs with unilateral femoral head and neck ostectomy through standard clinical evaluation and using a pressure-sensitive walkway. The hypothesis was that these dogs exhibit changes in kinetic and temporospatial parameters due to the surgical procedure that may detected by Symmetry Index (SI). Thirty dogs divided into two groups were used: G1 had 15 clinically healthy dogs; G2 had 15 dogs that underwent unilateral femoral head and neck ostectomy performed through access craniolateral and without muscle interposition. The velocity was maintained from 0.9-1.1 m/s and acceleration from -0.15 to 0.15 m/s2. Five valid trials were analyzed for each dog. The peak vertical force, vertical impulse, gait cycle time, stance time, swing time, stride length, and the percentage body weight distribution among the four limbs were determined. The Symmetry Index was calculated between limbs for each variable in G1 and G2. After this, Symmetry Indices were compared between Groups. Limb function (G2) was considered excellent in 10 dogs, good in four, and fair in one case. The operated limb was shortened and circumferential measurement of the thigh was lesser compared to contralateral limb. Hip extension was limited. In radiographic examination, displacement of the proximal femur was observed in all operated limbs. Statistical differences were observed for the Symmetry indices between G1 and G2 in several temporospatial parameters. Impulse was statistically different comparing SI of the G1 hind limb/forelimb with G2 operated hind limb/ipsilateral forelimb and G2 operated hind limb/diagonal forelimb. In conclusion, dogs with unilateral femoral head and neck ostectomy have changes mostly in temporospatial parameters that may be detected by SI, despite good functional results